Six Sigma and HIRARC Analysis in CNC Cutting Process: Analisis Six Sigma dan HIRARC dalam Proses Pemotongan CNC - Bimantoro, Raihan Daru; Aidil, Joumil (Academia Open, 2026)
General Background The steel fabrication industry requires precise production quality and reliable occupational safety to maintain competitive manufacturing performance. Specific Background In the CNC cutting process, product defects and workplace hazards remain critical issues because cutting activities involve metal processing, heat exposure, heavy components, and operator safety risks. Knowledge Gap Previous studies commonly examine Six Sigma quality control and HIRARC safety assessment separately, while integrated analysis in CNC cutting operations remains limited. Aims This study analyzes product quality through Six Sigma and identifies occupational hazards through HIRARC in the CNC cutting process. Results The findings show that cut surface defects are the most dominant defect category, reaching 53.57% of total defects. The process recorded an average DPMO of 28,745 and a sigma level of 3.41, indicating moderate process capability. HIRARC identified nine potential hazards, consisting of two high risks, five moderate risks, and two low risks. Novelty The study integrates Six Sigma and HIRARC to examine quality performance and occupational safety within one analytical framework. Implications The findings support integrated technical control, standard work procedures, ergonomic improvement, and risk control to improve productivity and operational safety simultaneously. Highlights: Cut surface problems reached 53.57% of total defects. Average DPMO was 28,745 with a 3.41 sigma level. Nine hazards were classified into high, moderate, and low categories. Keywords: CNC Cutting, Six Sigma, DPO (Defect per Opportunity), DPMO (Defect per Million Opportunities), HIRARC